2021
DOI: 10.30919/esee8c416
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Solar Energy Full Spectrum Conversion and Utilization

Abstract: Photovoltaic technology is a direct and effective way to utilize solar energy. The mismatch between the absorption band of solar cells and the solar light band restricts solar energy's efficient use. Full-spectrum conversion of solar energy with spectral modification and coupling solar thermal application are reviewed. Additionally, implementing machine learning (ML) methods to improve solar energy utilization is also examined. With the utilization of up-conversion materials for solar cells, the solar-energy-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…This study demonstrated utilizing renewable energy as offset to reduce CO2. In addition, many studies were conducted to capitalize the advance of integration of solar energy and thermal application to fossil fuel power plants (Chen et al, 2021).…”
Section: Fuel Consumption and Co2 Emissionsmentioning
confidence: 99%
“…This study demonstrated utilizing renewable energy as offset to reduce CO2. In addition, many studies were conducted to capitalize the advance of integration of solar energy and thermal application to fossil fuel power plants (Chen et al, 2021).…”
Section: Fuel Consumption and Co2 Emissionsmentioning
confidence: 99%
“…These robust alternative approaches can predict complicated processes without solving theoretical equations. Nowadays, ML methods have been utilized in various areas due to their excellent performance with acceptable accuracy and reliability 32 38 .…”
Section: Introductionmentioning
confidence: 99%
“…With utility of recent generation and ecological knowledge, the neighborhood assets may beefed on without a great deal damage to environment. [5][6][7] The renewable assets encompass wind power, sunpower, biomass power, biogas etc. Power technology zone may be very vital in Indian financial system and it's far growing rapidly.…”
Section: Introduction-mentioning
confidence: 99%